The appropriate use of human albumin in a Brazilian University Hospital: therapeutic indication and dosage regimen - Tatiane Sayuri Ishida; Maria Cristina Sakai; Daniela Oliveira de Melo (Brazilian Journal of Pharmaceutical Sciences, 2019)
The objective of the study was to evaluate the use of human albumin in a Brazilian university hospital, in compliance with the institutional protocol and other clinical guidelines, taking into account the therapeutic indications and the dosage regimens. Data was obtained from the pharmacy dispensing records of human albumin, the requests for use it and, when available, the patient’s records between January and October 2017. After evaluation the therapeutic indications and the dosage regimens were classified as “appropriate” and “inappropriate”. The analysis of 98 requests showed that, when compared to the institutional protocol, 54 (55.1%) requests had an inappropriate therapeutic indication. However, when a comparison was made between 25 medical records (54 requests) and other clinical guidelines, it was observed that the therapeutic indication had none classified as inappropriate. In addition, 16 (29.7%) requests were considered inappropriate in relation to dosage regimens. From these results, it was possible to conclude that although the use of human albumin in the hospital was associated to a clinical protocol, it was outdated. Thus, it is possible to affirm that not only the adoption of a clinical protocol, but its periodical updating is an important strategy to promote the rational use of drugs.